Peran Teologi Paulus dalam Roma 9-11 bagi Identitas Kristen di Tengah Realitas Israel Modern - Bangun, Grace Yunita Apulina (JURNAL LUXNOS, 2025)
This study aims to analyze Pauline theology in Romans 9–11 as a foundation for forming a responsible Christian identity amidst the reality of modern Israel. The research employs a qualitative method through literature study, exegetical-theological analysis, and a contextual theological approach. The results indicate that Paul rejects two extremes: Supersessionism, which negates the significance of Israel in salvation history, and uncritical Christian Zionism, which directly identifies the modern State of Israel with the will of God. Through the concept of the "Remnant of Israel" and the "Olive Tree" metaphor, Paul affirms the continuity of God's salvific work toward Israel while simultaneously upholding the universality of the Gospel in Christ. These findings emphasize that Christian identity must value the Jewish roots of the Christian faith, reject anti-Semitism, avoid religious nationalism, maintain the finality of Christ, and remain faithful to the calling of mission, justice, peace, and humanity. Consequently, Romans 9–11 provides a theological framework for the 21st-century global Church to respond to the reality of modern Israel in a Christocentric, historical, and ethical manner.